Clinical pharmacokinetic and pharmacodynamic analysis of daptomycin and the necessity of high-dose regimen in Japanese adult patients. Issue 6 (June 2019) - Urakami, Toshiharu; Hamada, Yohei; Oka, Yusuke; Okinaka, Tomohide; Yamakuchi, Hiroki; Magarifuchi, Hiroki; Aoki, Yosuke
Abstract: The objective of this study was to explore the optimal dosage regimen of daptomycin and to determine the necessity and validity of a high-dose regimen from the perspectives of PK/PD parameters using Monte Carlo Simulation (MCS) and therapeutic drug monitoring (TDM) in a Japanese clinical setting. The volume of distribution (0.13 ± 0.012 L/kg) in this study was greater than that in healthy volunteers reported in Japan. The range of half-lives was between 8.9 and 34.9 h, which were gradually prolonged as creatinine clearance decreased. In MCS, the cumulative fractions of response (CFR) of the peak/MIC ≧ 60 and the AUC/MIC ≧ 666 at the 6 mg/kg q 24 h were 72.0% and 78.8% but at the 10 mg/kg q 24 h, the CFRs improved to both 99%. In TDM with 6 mg/kg q 24 h regimen, the patients who reached the peak and AUC target were 40% (2 out of 5 patients), respectively. The intraindividual variability in daptomycin PK may indicate the necessity of TDM and high-dose regimen, such as over 8 mg/kg, may be needed to ensure the effectiveness especially on Japanese patients with normal renal function.